Electronic Stamp Validity: Cyber Law Perspective on the Effectiveness of E-Stamp Usage in E-commerce Transactions - Sirait, Resmaya Agnesia Mutiara; Nugraha, Adhytia; Serah, Yenny Aman; Marpaung, Samuel (Reformasi Hukum, 2024)
Digitalization is an era that has triggered many profound changes to all aspects of daily activities. The shift of the business world to the digital era has more or less changed the activity of buying and selling transactions from the traditional market to the digital market known as e-commerce, which is currently widely used by consumers in shopping activities. E-commerce is a technology medium widely used for buying and selling products on small and large scales. Buying and selling products or online business transactions through large-scale e-commerce requires proof of a binding agreement using digital stamps (e-stamps). This study analyzes how effective e-stamp duty is in online business transactions through e-commerce. This research is based on normative legal research using a normative juridical approach. The results of this study show that, regarding the validity of e-stamps, they have the same legal value as sticky stamps and cannot be contested. E-stamps in online business transactions through e-commerce contribute significantly to effectiveness and efficiency when viewed from cyber law. The researcher recommends further studying the effectiveness of using e-stamp duty in online business transactions (e-commerce), as reviewed by cyber law.